Control of a service satellite during its mission on space debris removal from orbits with high inclination by implementation of an ion beam method. (May 2022) - Obukhov, V.A.; Kirillov, V.A.; Petukhov, V.G.; Pokryshkin, A.I.; Popov, G.A.; Svotina, V.V.; Testoyedov, N.A.; Usovik, I.V.
Abstract: The largest population of space debris is observed in the low-Earth-orbit region with altitudes of 600–1000 km and inclinations of 80–100°. As follows from the predictive calculations, space debris removal from this region exactly is of the first priority. For this reason, our article discusses the problems of controlling the motion of service spacecraft – space debris object cluster when the space debris object is removed from a low orbit with high inclination. In the conceptual design of the spacecraft presented hereinafter, the electric propulsion system contains two electric propulsion thrusters of stationary plasma thruster type, each of which is mounted with the possibility of independent rotation respect to two mutually perpendicular directions. An ion beam injector forms an ion beam with 65 mN of thrust. Spacecraft motion control, including the thrust vector control, is provided by coordinated rotation of thrusters. For such concept, a strategy and an algorithm for controlling the motion of the spacecraft center of mass are proposed, which are based on the control of the spacecraft lateral and longitudinal motion that is understood as the control of the relative distance between the spacecraft and the space debris object. The strategy of spacecraft lateral motion control assumes that due to the thrusters' rotation the spacecraft should be displaced in such a way that the vector of the relative range between the spacecraft and the space debris object coincides with the direction of the transversal of the orbital coordinate system. For the practical implementation of the control, an algorithm has been developed for controlling the thrusters' rotation to create the required values of the spacecraft acceleration projections. The mathematical model includes the equations of motion of the spacecraft center of mass taking into account the aerodynamic deceleration. The solar panels' orientation to the Sun is provided by the spacecraft roll rotation relative to its longitudinal axis and turning the solar panels relative to their axis of rotation. The change in the ion beam momentum transfer is considered using a simple simulation model. Mathematical modeling was performed for the following parameters of the initial orbit: altitude: 800 km; eccentricity: 0.0005; and inclination: 90 0 . For the proposed control algorithm, a range of possible thrust of a single thruster was 51–60 mN. The simulation results show that the proposed control can be used to remove space debris object from low orbits with high inclination, taking into account the roll spacecraft rotation to keep the solar panels' orientation to the Sun. Highlights: Control a spacecraft (SC) for cleaning the LEO region from space debris objects (SDO). The strategy of SC lateral motion control due to two electric propulsion rotation. Solar panel (SP) orientation to the Sun providing by the SC roll rotation. The mathematical modelling taking into account the aerodynamic deceleration.